PENGARUH PEMERAMAN, PENGERINGAN, DAN KEBERADAAN SARCOTESTA TERHADAP PERKECAMBAHAN BENIH PEPAYA (Carica papaya L.) VARIETAS CALLINA - Amelia Sebayang; T. Chairun Nissa B; Nini Rahmawati (Universitas Sumatera Utara, 2014)
This research aims to obtain the best fruit ripeness, seed drying and the effect of removal ofsarcotesta on germination of papaya seed, variety Callina. This experiment was conducted in theSeed Technology Laboratory, Agriculture Faculty, University of Sumatera Utara during July-September 2013, A factorial randomized block design with 3 factors and 3 replications was used.The factors were fruit ripening (0, 2, 4 days), seed drying (0, 1, 2) days and removal of sarcotesta.Variables observed were germination rate (%/etmal), total germination (%), normal seedlingpercentage (%), seedling fresh weight (g), height of sprout (cm), and peak value of germination(%/day). The results showed that ripening increased rate of germination, total germination, normalseedling percentage, seedling fresh weight and peak value. Interaction between ripening and seeddrying increased height of sprout. The highest germination was obtained for treatments of withoutfruit ripening, without seed drying, and without sarcotesta.Keywords : papaya, ripening, seed drying, sarcotesta.